Filmer la prison et ses personnels. D'une approche expérimentale à une démarche concertée - Jean-Lucien Sanchez (Criminocorpus)
The Criminocorpus History of Justice, Crime and Punishment Museum offers interactive tours of prisons. The first online was that of the prison of Le Havre in 2010, followed five years later by that of Paris La Santé. To these two achievements has just been added in 2022 the interactive tour of the prisons of Colmar and Mulhouse, which constitutes the beginning of a new dynamic. Indeed, the Directorate of Prison Administration has implemented an ambitious policy to promote its heritage and its history through the realization of interactive tour of all its prisons dedicated to closure. This impulse has made it possible to change the rhythm of these achievements which, from experimental and episodic, have become standardized and systematic. This article aims to present the field work and the different stages of a long process that led to this outcome.